2020
DOI: 10.1155/2020/9589507
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-cysteine and Mechanisms Involved in Resolution of Chronic Wound Biofilm

Abstract: Chronic wounds are a major global health problem with the presence of biofilm significantly contributing to wound chronicity. Current treatments are ineffective in resolving biofilm and simultaneously killing the bacteria; therefore, effective biofilm-resolving drugs are needed. We have previously shown that, together with α-tocopherol, N-acetyl-cysteine (NAC) significantly improves the healing of biofilm-containing chronic wounds, in a diabetic mouse model we developed, by causing disappearance of the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Zhao [19] 2019 β-cyclodextrin X X Abbas [45] 2019 X Mei [46] 2017 Nanofibers polypropylene X X Curcumin + N-acetyl-cysteine Castro [47] 2015 Galactomannan X X Castro [48] 2017 Galactomannan X (Obs) Jimenez-Garcia [49] 2018 Galactomannan X (Obs) Jimenez-Garcia [50] 2021 Galactomannan X (Obs) [52] 2020 Microbiota X…”
Section: Curcumin + Chitosanmentioning
confidence: 99%
“…Zhao [19] 2019 β-cyclodextrin X X Abbas [45] 2019 X Mei [46] 2017 Nanofibers polypropylene X X Curcumin + N-acetyl-cysteine Castro [47] 2015 Galactomannan X X Castro [48] 2017 Galactomannan X (Obs) Jimenez-Garcia [49] 2018 Galactomannan X (Obs) Jimenez-Garcia [50] 2021 Galactomannan X (Obs) [52] 2020 Microbiota X…”
Section: Curcumin + Chitosanmentioning
confidence: 99%
“…In this work, three types of natural substances (NAC, RLs, and UA) were tested for their ability to inhibit bacterial growth, prevent biofilm formation, and reduce biofilm mass of four selected bacterial food-borne pathogens (Gram-positive L. monocytogenes, S. aureus, and Gram-negative E. coli, S. enterica Infantis, and Enteritidis). Information regarding the antimicrobial efficacy of NAC, RLs, and UA against food-borne pathogens is sparse; however, all the substances previously showed promising antimicrobial efficacy against other pathogens [15][16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In the db/db −/− chronic wounds, biofilm starts to form around 3 days after wounding and induction of OS in the wound tissue. The wounds became fully chronic within 20 days and contained mature biofilm, comprised of bacteria and extracellular polymeric substance (Dhall et al, 2014;Li et al, 2020), also found in human diabetic chronic wounds.…”
Section: Introductionmentioning
confidence: 89%